Expanding the substrate specificity of peptide asparaginyl ligase - Chua, Niying (Nanyang Technological University, 2023)
Through amide bond formation, peptide ligases (such as sortase A and subtiligase) introduce specific protein modifications, providing a specific and affordable tool for protein conjugation. Although sortases and subtiligases are capable of site-specific protein conjugations, their slow ligation reaction rate and dependence on cofactors make them difficult to use extensively. Butelase 1, the first Peptide Asparaginyl Ligase (PAL) discovered, exhibits a high ligation catalytic efficiency, significantly outperforming sortase A and subtiligase. Other cyclotide-producing plants have been found to have PAL homologs, such as Oldenlandia affinis and Viola yedoensis (OaAEP1b and VyPAL2 respectively), as well as the catalytically efficient mutant OaAEP1b C247A. In spite of their structural similarities, these PALs have a narrow substrate specificity requiring a hydrophobic residue at P2, which limits their application downstream. In order to efficiently synthesize dually labeled proteins sequentially or one-pot, it would be interesting to engineer PALs with mutually exclusive substrate specificities. To expand the current repertoire of recombinant PALs, protein engineering methods like directed evolution was utilized. Directed evolution experiments were conducted by introducing random mutations at the S2ʹ pocket of OaAEP1b C247A and subsequently screening for mutants with relevant activity. We designed and implemented a screening strategy involving the display of enzymes on the cell surface and the detection of active ligases through FRET assays.Using this approach, we were able to identify three novel PALs with varying substrate specificities. The characterization of the mutants provide valuable insights into the design of more efficient recombinant PALs for biotechnological applications.